2018
DOI: 10.1186/s12879-018-3032-x
|View full text |Cite
|
Sign up to set email alerts
|

Rubella seroprevalence among pregnant women in Beijing, China

Abstract: BackgroundRubella infection in pregnant women can result in serious effects, such as miscarriages, stillbirths, and congenital rubella syndrome (CRS). However, very little is known about the rubella seroprevalence among pregnant women in China.MethodsThis is a cross-sectional and hospital-based study. From June 2016 through March 2017, a total of 324 serum samples from healthy pregnant women were collected in the Shunyi Women and Children’s Hospital of Beijing Children’s Hospital. Rubella-specific IgG antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
5
7
2
Order By: Relevance
“…The prevalence rates of anti-Rubella antibodies in this study correlated with studies reported from Bangladesh, a socioeconomically similar country like India [16]. Only a few studies, which included one from Pakistan (16%) and another from Tanzania (<5%), revealed lower seroprevalence rates than those observed in the present study [17,19].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The prevalence rates of anti-Rubella antibodies in this study correlated with studies reported from Bangladesh, a socioeconomically similar country like India [16]. Only a few studies, which included one from Pakistan (16%) and another from Tanzania (<5%), revealed lower seroprevalence rates than those observed in the present study [17,19].…”
Section: Discussionsupporting
confidence: 86%
“…A study of the seroprevalence of Rubella-specific IgG antibodies among healthy pregnant women in China revealed that 83.3% of women had protective antibodies [17]. In a recent study from Cameroon, which evaluated the seroprevalence of Rubella-specific IgG antibodies among pregnant women found 94.4% seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…1,12 In this study, the seroprevalence of rubella immunity among Burkina Faso (77%). 1,4,13 However, the seroprevalence of rubella immunity in the current study was higher than findings from other countries like southern India (65%), Niger (53%), and lower than findings from Nigeria (97.9%), Mexico (97.1%), Turkey (96.1%), Spain (94.1%), Western Province in KSA (91.6%), Cameroon (88.6%) and Kuwait (88.4%). 1,3,14,15 The differences in seroprevalence between different studies could be attributed to the variation in the epidemiology of the infection, the differences in the sample size and the methodology of the studies, the utilised laboratory tests, discrepancies in the used cut-off points used to confirm the immunity, and the involvement of rubella immunisation in their national vaccination programs.…”
Section: Discussioncontrasting
confidence: 82%
“…In this study, the seroprevalence of rubella immunity among pregnant was 76.41%. A similar report has been released from other countries like Italy (85.8%), China (83.3%), Ethiopia (79.5%) and Burkina Faso (77%) 1,4,13 . However, the seroprevalence of rubella immunity in the current study was higher than findings from other countries like southern India (65%), Niger (53%), and lower than findings from Nigeria (97.9%), Mexico (97.1%), Turkey (96.1%), Spain (94.1%), Western Province in KSA (91.6%), Cameroon (88.6%) and Kuwait (88.4%) 1,3,14,15 .…”
Section: Discussionsupporting
confidence: 74%
“…The reason for this low rate is that Rubella vaccine is currently not included in the national immunization program (19) . In China, although this rate varies according to age in pregnant women, this rate is approximately 84.0% (20) . The high level of IgG antibody seropositivity in our country reveals that we have a successful vaccination policy compared with other developing countries.…”
Section: Discussionmentioning
confidence: 99%